2018
DOI: 10.1039/c8cp02943a
|View full text |Cite
|
Sign up to set email alerts
|

A mean-field theory on the differential capacitance of asymmetric ionic liquid electrolytes. II. Accounts of ionic interactions

Abstract: A size-asymmetric mean-field theory with ionic interactions is developed for the electric double layer of room temperature ionic liquid (IL) electrolytes, based on the previous work on non-interacting ions (Y. Han et al., J. Phys.: Condens. Matter, 2014, 26, 284103). By solving the modified Poisson-Boltzmann equation with some simplified assumptions following a recent work (Z. A. H. Goodwin et al., Electrochim. Acta, 2017, 225, 190-197), an analytical expression of differential capacitance can be derived, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…They give a possibility to consider systems beyond the assumptions of continuum models and to take into account a wide spectrum of interparticle interactions as well as to predict correlation effects using the statistical mechanics. It was shown that the voltage dependence of the differential capacitance obtained within the mean field approximation for the case of short-range interactions between ions is closer to experimental findings [47,48]. The importance of short-range interactions in a lattice model of ionic systems was demonstrated in [49], where the effect of competition between long-range Coulomb and short-range dispersion interaction on phase transitions was studied.…”
Section: Introductionsupporting
confidence: 59%
“…They give a possibility to consider systems beyond the assumptions of continuum models and to take into account a wide spectrum of interparticle interactions as well as to predict correlation effects using the statistical mechanics. It was shown that the voltage dependence of the differential capacitance obtained within the mean field approximation for the case of short-range interactions between ions is closer to experimental findings [47,48]. The importance of short-range interactions in a lattice model of ionic systems was demonstrated in [49], where the effect of competition between long-range Coulomb and short-range dispersion interaction on phase transitions was studied.…”
Section: Introductionsupporting
confidence: 59%
“…Extremely high ion concentrations in ionic liquids strongly increase the importance of short-range interactions and correlations. It was shown that with accounting of the short-range interactions on the mean field level in addition to the Coulomb ones the voltage dependence of the differential capacitance becomes closer to experimental findings [24,25]. An important influence of a competition of short-range dispersion (or van der Waals) and long-range Coulomb interactions on phase transitions in a lattice model of ionic systems was demonstrated in [26].…”
Section: Introductionmentioning
confidence: 59%
“…[11] In addition, a series of simulations have established the models which include the contribution of C H and C D (diffuse layer capacitance) to describe the experimental results of SLG in aqueous electrolytes. [12] It was found that the interfacial capacitance of polarized SLG electrodes changes with the degree of ion packing (the total number of anions and cations in the electrolyte bulk divided by total number of available sites at the electrode surface), ion-ion interaction (through a correlation length parameter) and size of ions in neat ionic liquids. [13] For instance, when the ion packing factor is high, C Q would control the interfacial capacitance near the potential of zero charge (pzc) without seeing the effect of ion-ion correlation, resulting in a camel-shape dependence of the total capacitance on the applied potential.…”
Section: Introductionmentioning
confidence: 99%